Nitrogen balances can help fine‐tune nitrogen management. Issue 5 (4th October 2018) - Maaz, Tai McClellan; Brown, Tabitha; Glover, Ayana; Brooks, Erin
Abstract : This article presents a framework for using nitrogen use efficiency within the context of yield and crop quality goals to evaluate fertilizer management. The framework's goal is to diagnose underlying factors contributing to the inefficient use of fertilizer. Earn 0.5 CEUs in Nutrient Management by reading this article and taking the quiz at www.certifiedcropadviser.org/education/classroom/classes/609 .